1965
DOI: 10.1017/s0022172400044922
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitrocomparison of the effect of some antibacterial, antifungal and antiprotozoal agents on various strains ofMycoplasma(pleuropneumonia–like organisms: P.P.L.O.)

Abstract: A study was made in liquid medium over 7 days at 37° C. of the inhibitory action of nineteen antibacterial, antifungal and antiprotozoal drugs on twenty strains ofM. gallisepticum, eight other avian mycoplasmata, six mammalian mycoplasmata, two saprophytic mycoplasmata and the L-form ofStreptobacillus moniliformis(L–1).The twenty strains ofM. gallisepticumfrom Britain and other countries showed a similar range of drug sensitivity except where resistant strains were included. Tylosin and demethylchlortetracycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

1967
1967
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 72 publications
3
13
0
Order By: Relevance
“…Some difficulty was experienced, however, in obtaining consistent end-points in MIC titrations with the gold-containing drugs. Similar difficulties in assessing the in-vitro activity of ATM against human urogenital-tract mycoplasmas and against numerous strains of M. gallisepticum have been reported previously (Robinson, Wichelhausen and Brown, 1952;Newnham and Chu, 1965 carry-over contrast to the gold-containing compounds, the tetracyclines displayed activity at very low levels against M. arthritidis and M. pulmonis even after 7 days' incubation. It can be seen from table I1 that all the drugs examined were predominantly mycoplasmastatic in action.…”
Section: Mic Tests and Mycoplasmastatic And Mycoplasmacidal Activitysupporting
confidence: 66%
See 1 more Smart Citation
“…Some difficulty was experienced, however, in obtaining consistent end-points in MIC titrations with the gold-containing drugs. Similar difficulties in assessing the in-vitro activity of ATM against human urogenital-tract mycoplasmas and against numerous strains of M. gallisepticum have been reported previously (Robinson, Wichelhausen and Brown, 1952;Newnham and Chu, 1965 carry-over contrast to the gold-containing compounds, the tetracyclines displayed activity at very low levels against M. arthritidis and M. pulmonis even after 7 days' incubation. It can be seen from table I1 that all the drugs examined were predominantly mycoplasmastatic in action.…”
Section: Mic Tests and Mycoplasmastatic And Mycoplasmacidal Activitysupporting
confidence: 66%
“…Gold keratinate was virtually inactive against M. pulmonis. The " zoning " phenomenon, which occurs in tests for antimycoplasmal activity of gold-containing compounds against certain mycoplasma species (Newnham and Chu, 1965 ;Davidson and Thomas, 1966), was not observed with M. arthritidis or M . pulmonis.…”
Section: Mic Tests and Mycoplasmastatic And Mycoplasmacidal Activitymentioning
confidence: 99%
“…The phenomenon was attributed to the acquisition of antibiotic resistance and this was confirmed in the report of Fahey in 1957. Mataney (1957, Osborn & Pomeroy (1958), Osborn et al (1960) and Newnham and Chu (1965) observed that different strains of mycoplasmas showed considerable variations in sensitivity to a given antibiotic, probably due to extended or improperly administered therapy. Domermuth (1958Domermuth ( , 1960, Osborn et al (1960), Kiser et al (1961) and Zanella (1966) used a number of antibiotics to study, both in vivo and in vitro, how antibiotic resistance was induced in Mycoplasma gallisepticum (Mg).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro sensitivity of M. gallisepticum (Mg) and M. synoviae (Ms) to antimicrobials has been the subject of a number of studies (for example : Newnham & Chu, 1965;Kleven & Anderson, 1971;Levisohn, 1981;Whithear et al, 1983;Jordan & Knight, 1984;Lin, 1987;Jordan et al, 1989;Kempf et al, 1989, Tanner & Wu, 1992. Recently, a number of quinolone antibacterial agents have been synthesized which show improved anti-mycoplasma activity over the quinolone compounds that were available hitherto (Hannan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%